Determinants of Islamic Banking Vulnerability in Indonesia from 2014 to 2020 - Muhammad Iqbal; Sunaryati Sunaryati; Hadri Kusuma (IAIN Salatiga, 2021)
This study aims to analyze the eﬀect of ﬁnancial performance and macro-economic on Islamic banks' vulnerability in Indonesia from 2014 to 2020. Data were analyzed using the Autoregressive Distributed Lag since their several variables in the economy are dynamic. The results showed that exchange rates and financing are the dominant factors that aﬀect the Islamic banks' vulnerability. Therefore, policymakers tend to identify ﬁnancial instability and try to avoid the crisis if detected. The Z-score variable in the previous periods (VUL) is another factor that aﬀects Islamic banks' vulnerability